The nonlinear refraction and nonlinear absorption in 4-(4,6-diaminopyrimidin-2-ylthio) substituted double-decker Lu(III) phthalocyanine - Yağlıoğlu, H. Gül; Arslan, Metin; Abdurrahmanoğlu, Şaziye; Ünver, Hüseyin; Elmali, Ayhan; Bekaroğlu, Özer (Elsevier BV, 2008)
Abstract A 4-(4,6-diaminopyrimidin-2-ylthio) substituted double-decker Lu(III) phthalocyanines ( 4 ) have been prepared and characterized by elemental analysis, IR, UV–vis and 1 H NMR spectroscopies. The nonlinear refractive index, nonlinear absorption and the optical limiting (OL) performance of the compound 4 in a 0.5 mm spectroscopic cell in DMF solution were investigated by using 4 ns pulse laser at 532 nm. Z-scan experiments have been conducted between 0.24 and 2.39 GW/cm 2 peak intensities for 10 Hz repetition rate and also between 2.39 and 23.89 GW/cm 2 peak intensities for 1 Hz repetition rate. The thermal effect contributes to the nonlinear response of the material higher than 0.72 GW/cm 2 peak intensity at 10 Hz. We measured the effective nonlinear refractive index of the material as 1.2×10 −11  esu at 3.5×10 −4  M concentration with the peak intensity less than 0.72 GW/cm 2 and we found that nonlinear absorption was very small. On the other hand, when concentration is increased to 2.4×10 −3  M material's nonlinear absorption becomes dominant mechanism for the nonlinear response and the compound 4 indicates OL behavior at 2.4×10 −3  M concentration.